Early local microcirculation is improved after intramedullary nailing in comparison to external fixation in a porcine model with a femur fracture - Kalbas, Yannik; Qiao, Zhi; Horst, Klemens; Teuben, Michel; Tolba, Rene H.; Hildebrand, Frank; Pape, Hans-Christoph; Pfeifer, Roman; Auner, B; Stormann, P; Relja, Borna; Marzi, I; et al. (European Journal of Trauma and Emergency Surgery, 2018)
Introduction: The local circulatory changes induced by intramedullary reaming are not fully understood. This study aimed to analyse the short-term local microcirculation associated with different surgical strategies in a porcine model with a mid-shaft fracture. Methods: German landrace pigs were subjected to a standardised femoral fracture under standard anaesthesia and intensive care monitoring. One group was subjected to intramedullary reaming and nailing (nail group), while a second group was stabilised with external fixation (fix ex group). Microcirculation [e.g. relative blood flow (flow), oxygen saturation and relative haemoglobin concentration] was measured in the vastus lateralis muscle adjacent to the fracture using an O2C (oxygen to see, LEA Medizintechnik GMBH) device at 0 (before fracture, baseline), 6 (90-min posttreatment), 24, 48 and 72 h. Results: A total of 24 male pigs were used (nail group, n = 12; fix ex group, n = 12). During the observation period, a significant increase of flow was found at 6 (P = 0.048), 48 (P = 0.023) and 72 h (P = 0.042) in comparison with baseline levels. Local oxygen delivery was significantly higher at 48 (P = 0.017) and 72 h (P = 0.021) in animals in the nail group compared to animals in the external fixation group. Conclusion: This study used a standardised porcine femoral fracture model and determined a significant increase in local blood microcirculation (e.g. flow and oxygen delivery) in animals treated with intramedullary reaming compared to external fixation. These changes may be of importance for fracture healing and local and systemic inflammatory responses. Further studies in this area are justified.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Femoral fracture; Intramedullary nailing; Microcirculation; Nailing; Osyteosythesis; Trauma